Etiology, epidemiology and environmental investigations on the causal factors of rubber tree (Hevea brasiliensis) bark necrosis: A physiological trunk disease caused by an accumulation of stresses - Nandris D; Abina J; Angui P; Chrestin H; Moreau R; Pellegrin F (Proceedings of IRRDB Conference: NR Industry: Responding to Globalization, 7-8 September 2004, Kunming International Convention & Exhibition Center, China. pp.407-421.)
Bark Necrosis (BN), first studied and described in Cote dIvoire in the 1980s, now affects most modern rubber plantations worldwide, with a wide range of severity across sites. While previous and recent etiological analyses remain non-conclusive, environmental factors were shown to be associated with BN. Indeed, numerous epidemiological surveys conducted in various African and Asian plantations on recently tapped blocks revealed the non-random location of the earliest single diseased trees. These risk areas are mainly characterized by the proximity of a swamp, plantation road, windrow, old bulldozer track, residual forest stump or slope break. In BN emergence areas, while no significant correlation was found with chemical soil parameters, physical soil analyses (e.g. penetrometry) revealed higher soil compaction, often associated with poorer rhizogenesis in BN trees. Furthermore, initial BN symptoms were preferentially observed near the grafted bud at the rootstock/scion junction (RS/S). Numerous comparative ecophysiological measurements of leaf water potential, stem water potential, and predawn base potential, using a PMS (plant moisture stress) pressure chamber, indicated water stress in BN trees. These results and preliminary dye transfer studies at the RS/S junction suggested a non-optimal vascular relation between the root system and the trunk of BN trees. Thus, compaction-associated reduced water availability of the soil, poor root capacity to meet the water drainage (latex flows) are now suspected to jointly act as the main exogenous casual stresses that induce the BN process at the RS/S bud zone, before spreading upward to the tapping cut. This multidisciplinary approach provides a new comprehensive scenario for the emergence of this multi-factorial physiological disease.
Keywords: Bark necrosis; Dryness; Ecophysiology; Epidemiology; Etiology; Physical constraints; Physiopathology; Soil-tree-disease interactions; Stress